O cuidado prestado a pessoas idosas com tuberculose a partir do discurso de cuidadores familiares - Alcantara, Lilia de Medeiros (2018)
Introduction: The Tuberculosis (TB) is considered as an issue of Public Health, with infectious diseases presenting the major mortality rate. As TB dissemination is related to the population ageing, there has been a displacement of the incidence for the elderly. Within this context, the caregiver is placed as a protagonist of care, taking the responsibility for supporting the activities performed by the elderly. Objective: To analyze the sense and the meanings in the discourse of the family caregivers related to care for elderly living in the city of João Pessoa-PB. Method: This is a qualitative study carried out between May and July 2018 in the city of João Pessoa – PB. The contributing subjects for the study were 6 family caregivers who took care the elderly while they were sick. The French Discourse Analysis was used for the empirical analyzes of the material. This study was approved in 2017 from the Research Ethics Committee of the Health Sciences Center of the Federal University of Paraíba, according to the evaluation report n° 2.303.511 with CAAE n° 76727317.7.0000.5188. Results: Two discursive blocks emerged: i) factors related to the management of tuberculosis and ii) difficulties related to the care developed by the caregivers. The discourses revealed the existence of a delay in the diagnosis of TB, that the gateway for the diagnosis is not the Primary Health Attention, as well as the frailties in the operationalization of the directly observed treatment, that is, the actions of TB control come up with obstacles in the realization of their attributes. Regarding the practice of management in the family dimension, it has been observed that there is an overload felt by the caregivers, that the stigma of the disease makes the care more difficult that the caregiver presents frailty in health and that the financial difficulties is presented as a negative implication in the provision of care. Final considerations: The discourses analyzed pointed out fragilities and difficulties in the care process offered; either by the health services or by the family members. Therefore, it is important that health professionals and health managers are sensitive to the aspects related to TB care in order to undo the knots found, as well as operationalize actions and strategies capable of offering greater support for the caregivers that are suffering from the overload of care.